2010
DOI: 10.2478/v10135-011-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of User Fees in Health Care System on Health Care Consumption

Abstract: Abstract:In comparison to other European countries, it is claimed that the Czech Republic belongs to the countries with higher health care consumption, even if health status does not positively correlate with health care use. Therefore, user fees as a form of patient cost sharing were introduced to regulate health care consumption and to confront the patient with resource scarcity in the health care system as a part of health care reform package in 2008. The goal of the paper is to determine the changes in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…As an instance, Italy implemented contracting out in health care but lack of strategic planning and restricted efficiency gains through high transaction costs led to decrease in access and no change in efficiency 54 . It is reported that lack of effective patient charters and complaints system and informal payments had a negative effect on access and efficiency in Czech Republic, Russia, Ukraine, and Armenia health care system 55,56 . In public health complexes, managers and employees don't have a competitive view.…”
Section: Discussionmentioning
confidence: 99%
“…As an instance, Italy implemented contracting out in health care but lack of strategic planning and restricted efficiency gains through high transaction costs led to decrease in access and no change in efficiency 54 . It is reported that lack of effective patient charters and complaints system and informal payments had a negative effect on access and efficiency in Czech Republic, Russia, Ukraine, and Armenia health care system 55,56 . In public health complexes, managers and employees don't have a competitive view.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of other market-type mechanisms in the dataset include user choice mechanisms and user charges in healthcare in the Czech Republic, Estonia and Hungary (Atun et al 2006;Krutilová 2010;Nagyistók 2010) liberalization and privatization across the EU and market-type mechanisms more generally (Audit Commission, 2002;Nemec and Kolisnichenko 2006). Unlike the studies on contracting out and quasi-market arrangements, where evidence on deteriorated public service equity was minimal, 50% of the cases of other market-type mechanisms documented some evidence on decreased equity (Table 7).…”
Section: Other Market-type Mechanismsmentioning
confidence: 99%
“…A possible explanation for this observation is that unlike other forms of market-type mechanisms, which concern how a public service is provided and by whom, user charges and user choice are more closely related to access to services. For example, the introduction of user charges (co-payments) in primary healthcare in Czech Republic led to a decrease in the use of some services (Krutilová 2010). A 26% drop was documented in primary home care visits compared to ordinary consultations, and a significant decrease in the use of medication (30.17% in 2008 and 27.65% in 2009).…”
Section: Other Market-type Mechanismsmentioning
confidence: 99%
“…by increasing the price paid by the individual at the time of consumption. The overwhelming majority of studies conducted in developed countries conclude that cost-sharing reduces demand for preventive services (Christensen, 1995;Friedman et al, 2002;Kiefe et al, 1994;Krůtilová, 2010;Lundberg et al,1998;Nexøe et al, 1997;Solanki et al, 2000;Stoner et al,1998). Similarly, for studies conducted in low-and middle-income countries (LMICs), the evidence suggests that the introduction or increase in user fees has almost and everywhere led to a decrease in utilisation (Schokkaert and Van de Voorde, 2011;Cohn and Dupas, 2010;Borghi et al, 2006;Souteyrand et al, 2008) Economic theory further predicts that cost-sharing generates adverse distributional consequences as low income individuals reduce utilisation more than the remaining population.…”
Section: Introductionmentioning
confidence: 99%